Synthesis of symmetrical hexagonal-shape PbO nanosheets using gold nanoparticles - Zeng, Shuwen (2014)
Anisotropic growth of PbO with symmetrical hexagonal-shape nanosheet morphology was demonstrated for the first time via solution phase synthesis in the presence of Au nanoparticles at room temperature. Au NPs play a critical role in the formation of PbO nanosheets. No nanosheets were formed in absence of Au NPs. The effect of Au NPs appears to result from their ability to provide nucleation sites to seed anisotropic growth of the PbO nanocrystals and later the nanocrystals aggregated to form nanosheet structure. The method demonstrated here provides a facile room temperature colloidal method of producing high-quality and yield of high-symmetrical hexagonal-shape PbO nanosheets with controlled edge length.